Short communicationEvaluation of the dental status in patients referred for heart surgery – a preliminary report - Jegier, Michał; Smalc, Aneta; Ciesielski, Piotr; Jander, Sławomir; Jegier, Bogdan (Archives of Medical Science, 2006)
The authors examined the oral health status in 100 consecutive patients of the Department of Cardiac Surgery, Medical University of Lodz, referred to scheduled heart operations. 26% of them were edentulous and they did not undergo closer clinical examination. Patients with natural dentition made 74% of the examined group. Oral hygiene in majority of the cases was not satisfactory – in 64% of the patients calculus and accompanying gingivitis were found. 17% of patients had neither treated nor removed roots. A DMF (Decay Missing Filled) index and treatment index were calculated in these patients as well. Mean values of the DMF index are: D – 3, M – 17, F – 4. The mean value of the treatment index equals 0.57. Lymphadenopathy was observed in 42% of cases. Our findings indicate that during qualification to a heart surgery dental examination and treatment should be considered.